Impact of Branding on Organizational Performance in the Not-for-Profit Sector - Verma, Sanjeev; Deou, Babita (Indian Journal of Marketing, 2007)
Market orientation is the implementation of marketing activities. There have been significant studies done in the past that define the concept of market orientation, its need, benefits and consequences. The available literature also provides enough support to establish the link between market orientation and organizational performance where high market orientation has been linked to higher business performance. Despite these findings, there is a need to further explore this relationship since most of the previous studies have focused on building this relationship in for-profit sector. The not-for-profit sector differs from the for-profit sector in not only the objectives but also in the implementation of market orientation philosophy. Therefore, the present study adopts a secondary research approach to understand the impact of market orientation on organizational performance in the not-for-profit sector, which then builds a foundation to further examine how one of the key elements or measures of market orientation i.e. Brand management is linked with market orientation. And, how does branding impacts organizational performance by facilitating market orientation.